2010
DOI: 10.1186/1471-2458-10-610
|View full text |Cite
|
Sign up to set email alerts
|

Self-medication with antibiotics for the treatment of menstrual symptoms in southwest Nigeria: a cross-sectional study

Abstract: BackgroundSelf-medication with antibiotics is an important factor contributing to the development of bacterial antibiotic resistance. The purpose of this study was to evaluate the prevalence of self-medication with antibiotics for the treatment of menstrual symptoms among university women in Southwest Nigeria.MethodsA cross-sectional survey was administered to female undergraduate and graduate students (n = 706) at four universities in Southwest Nigeria in 2008. The universities were selected by convenience an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
68
5
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(92 citation statements)
references
References 20 publications
11
68
5
2
Order By: Relevance
“…The most important reasons for self-medication in this study were found to be affordability (34.52%) and low severity of illness (26.19%).These findings are in line with the results of studies in jimma town 10 Analgesics were the most commonly consumed group of drugs 34(40.96%) which is comparable with the results of the study in Jimma University 12 and Addis Ababa where analgesics were used by 49.38% and 33.1% of the study participants respectively 1 . Antimicrobials were the second most commonly used medicinal groups 20(24.10%) which is consistent with studies in Addis Ababa (26.4%) 1 and south west Nigeria (24%) 19 .…”
Section: Discussionsupporting
confidence: 87%
“…The most important reasons for self-medication in this study were found to be affordability (34.52%) and low severity of illness (26.19%).These findings are in line with the results of studies in jimma town 10 Analgesics were the most commonly consumed group of drugs 34(40.96%) which is comparable with the results of the study in Jimma University 12 and Addis Ababa where analgesics were used by 49.38% and 33.1% of the study participants respectively 1 . Antimicrobials were the second most commonly used medicinal groups 20(24.10%) which is consistent with studies in Addis Ababa (26.4%) 1 and south west Nigeria (24%) 19 .…”
Section: Discussionsupporting
confidence: 87%
“…Of medications consumed for self treatment in Nigeria, it accounted for 63.4% in an urban slum 62 , 44% among urinary tract attendees prior to hospital admission 63 , 39% among medical undergraduates 64 and 24% for treating menstrual symptoms 65 . In addition, it accounted for a substantial percentage of diarrhoea treatment.…”
Section: Scope and Distributionmentioning
confidence: 99%
“…For instance, there is a positive correlation between level of education and self medication 16,18,24,65,89,98,99 . The trend of consulting patent medicine dealers for prescription decreases with acquisition of more formal education 24,98,100 .…”
Section: Self Medication -Sociodemographic and Medical Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Medicines for selfmedication are often called " non-prescription" or "over the counter (OTC) " products and are available without a doctor"s prescription through pharmacies. Medicines that require a doctor"s prescription are called prescription products (Sapkota et al, 2010 World-wide survey of consumers, 2006).…”
Section: Introductionmentioning
confidence: 99%